Reliability and validity of the Pragmatics Observational Measure (POM): A new observational measure of pragmatic language for children - Cordier, Reinie; Munro, N.; Wilkes-Gillan, S.; Speyer, R.; Pearce, W. (Pergamon, 2014)
There is a need for a reliable and valid assessment of childhood pragmatic language skills during peer–peer interactions. This study aimed to evaluate the psychometric properties of a newly developed pragmatic assessment, the Pragmatic Observational Measure (POM). The psychometric properties of the POM were investigated from observational data of two studies – study 1 involved 342 children aged 5–11years (108 children with ADHD; 108 typically developing playmates; 126 children in the control group), and study 2 involved 9 children with ADHD who attended a 7-week play-based intervention. The psychometric properties of the POM were determined based on the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) taxonomy of psychometric properties and definitions for health-related outcomes; the Pragmatic Protocol was used as the reference tool against which the POM was evaluated. The POM demonstrated sound psychometric properties in all there liability, validity and interpretability criteria against which it was assessed. The findings showed that the POM is a reliable and valid measure of pragmatic language skills of children with ADHD between the age of 5 and 11 years and has clinical utility in identifying children with pragmatic language difficulty.